Dispute in the South China Sea beetwen America and China - Zahran Hilman Salim B.Pawe; Seniwati Seniwati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The South China Sea dispute is one of the most complex and strategic geopolitical conflicts, involving rivalry between the United States and China, as well as a number of countries in the region. The strategic geographical position of the South China Sea as The strategic geographical position of the South China Sea as the world's main shipping lane, the wealth of natural resources such as oil and gas, and the overlapping claims over the exclusive economic zone (EEZ) make it an area with very high economic, political and military interests. From a political perspective, the conflict reflects a global power struggle, in which China is strengthening its claim through infrastructure development, military modernization, and an aggressive foreign policy under the leadership of Xi Jinping. under the leadership of Xi Jinping. On the other hand, the United States, along with strategic alliances such as the Quad, seeks to contain China's expansion by increasing its military presence in the Indo-Pacific region. This rivalry is exacerbated by regional dynamics involving ASEAN countries, as well as the struggle for global influence between the two major powers. This research analyzes the main factors influencing the escalation of the South China Sea dispute, including the role of geopolitics in the disputes, including their geopolitical, economic and military roles, and their implications for regional stability and the global balance of power. The study provides a comprehensive insight into a conflict that not only affects the main actors, but also the international security architecture. also to the international security architecture.